Mental health care needs in cystic fibrosis: A scoping review. (7th February 2022) - Tickner, Campbell; Holland, Lucy; Wark, Peter; Hilton, Jodi; Morrison, Cathy; Kay-Lambkin, Frances; Heinsch, Milena
ABSTRACT: People with cystic fibrosis experience rates of anxiety and depression that are considerably higher than those of the general population. Research suggests low mental health functioning can lead to poor health outcomes and quality of life for this population. Consequently, recognition of the need for routine mental health screening and referral in cystic fibrosis care is increasing. Yet to date, less is known about the actual mental health care needs of people with cystic fibrosis. This scoping review sought to address this gap by examining the mental health care needs of adults and adolescents living with cystic fibrosis, and how are these needs are (or are not) being met. Findings suggest current efforts at mental health care provision do not adequately meet the needs of people with cystic fibrosis, highlighting the urgency of conducting high quality intervention research to support effective mental health care for this population.